Commodification and Slavery in the Nineteenth-Century Indonesian Archipelago. Issue 1 (4th September 2020) - Bosma, Ulbe
Abstract: Slavery did not simply die slowly in the nineteenth century; in some parts of the world, it expanded. Engaging with the literature on slavery in the Indian Ocean in the nineteenth century, this article explains how a rising demand for forest and sea products, pepper and rice, together with a proliferation of firearms, kindled slave raiding and trading in the Indonesian archipelago. Enslavement happened both through capture and debt traps. This article offers an estimate of the number of annually enslaved in the Indonesian archipelago during the mid-nineteenth century and relates this to a conjectured total slave population of this particular region. The commercialization of slavery must have fundamentally changed the character of customary institutions of bondage. The article cites contemporary sources about the conditions of the captives and concludes with an explanation of how commercial slavery in this part of the world could continue into early years of the twentieth century.